Commentary on Bowe et al, "The State of the Otolaryngology Match: A Review of Applicant Trends, 'Impossible' Qualifications, and Implications". (1st February 2018) - Bhalla, Vidur; Sykes, Kevin J.; Kraft, Shannon M.; Chiu, Alexander G.
Abstract : An objective evidence‐based review of the metrics used to evaluate applicants entering our field ultimately found these figures to have upward trends without any major correlation to performance in residency. The rise of these metrics coincides with a yearly drop in senior applicants, and in 2017, nearly 10% of programs did not match their contingent. The causes of unmatched spots must be examined to ensure that the field of otolaryngology can continue to grow and attract medical students who will excel in our field. Considerations into revising the applicant selection process, early introduction and mentorship within the otolaryngology field, and changes to the current otolaryngology interview process are discussed.